Educação, política e responsabilidade pelo mundo: reflexões sobre o ensino de filosofia na Escola Estadual de Educação Profissional Francisco Paiva Tavares - Freitas, Kassyo Mikaelson Ribeiro de (2024)
In this research work we pursue as a general objective, to lead the community to be interested in the development in the process of a quality education, participating in decision making, choices that can highlight the improvement of satisfactory public education for all, in the search for the struggle of the rights of all and consistency in the formation for the lower classes, by op portunizing the integral development of the individual, from the concepts of thinkers and philosophical reflections. To this end, we assume the theme researched highlights: Education, politics and responsibility for the world: reflections on the teaching of Philosophy in the State School of Professional Education Francisco Paiva Tavares. This theme is supported in Freire (1987) as well as in Arendt (2016). We applied the method of qualitative analysis, with the application of a questionnaire to a class of 2 9 participants, from the 3rd Series of High School of Technical Course in Informatics, from the State School of Professional Education Francisco Paiva Tavares, from the city of Charity, in Ceará, to the data collected. This dissertation is divided into thr ee chapters. In the first chapter, we deal with the work Pedagogy of the Oppressed of Freire (1987), with regard to the problematizing and liberating contradiction of education. Human world relations, generating themes and the problematizing content of thi s education. In the second chapter, we reflect on what Freire (2011) expresses in the Pedagogy of Autonomy about which teaching requires the conviction that change is possible. Teaching requires understanding that education is a form of intervention in the world. And in the third and final chapter, we address what Arendt (2016) points out to us in his book Between the Past and the Future about the crisis in education. We conclude that the discipline of Philosophy is, in this sense, a contribution to such reflection, debate, criticality, questioning and effective action, becoming an instrument of social transformation of great value to collaborate with the public school, to be considered in the union between school and family in the development of the common good and in the delivery of public policies in quality education to the community. That is, the transition of the student who goes through the school, valuing it in a critical and participatory citizen, as well as a trained professional who can generate good fruits of transformation in the environment he lives, whether in the labor market, or in the university, or collaborating in the most diverse practices of citizenship.